A new ethylene receptor from the bark tissues of Hevea brasiliensis - Sreelatha S; Hall PBrenda; Jacob J; Krishnakumar R; Kristine Hill; Luke L.P; Sathik M.B.M; Schaller EricG (Rubber Science, 2013)
Stimulating rubber trees by applying athephone in the bark is a common practise to increase the latex yield in rubber plantations. The ethylene generated from ethephon induces various physiological and biochemicalchanges and eventually leads to increased latex production. Ethyee perception and signal transduction is initiated when the ethylene molecules bind with the receptors localized in the cell membranes. Information on ethylene receptors and the molecules mechanism involved in the signal transduction is important to understand the regulation of latex flow in the Hevea after stimulation. The relative expression of an ethylene receptorgene (Hb ETR1) in unstimulated and stimulated trees of Hevea clone RRII 105 using relative RT PCR indicated that the gene was up regulated after stimulation with ethephon. Phylogenetic analysis of the ethylene receptors identified from plant species and by using a PCR with degenerate primers, a new ethylene receptor was identified in the bark tissues of Hevea which was named as Hb ETR2. The gene representing this receptor was also found to br up regulated by ethylene stimulation. qRT-PCR also showed up- regulation of these immediately after stimulation.
Keywords: Bark tissue; Degenerate PCR; Ethylene receptor; Phylogenetic tree